ELTE 375 - Beszámoló az ELTE centenáriumáról - Gosztonyi, Gergely (Gerundium, 2011)
Budapest’s Eötvös University is 375 years old—Report on ELTE ’s Anniversary Celebration. In 2010 Eötvös Loránd University, Hungary’s oldest continuously operating institute of higher education, celebrated the 375th anniversary of its foundation. The university’s legal predecessor was established in Nagyszombat in 1635 by Péter Pázmány, Archbishop of Esztergom. The text describes the major stages of the preparation for the year of jubilee and the most significant events of the festive year. The chief purpose of the series of events, it is stated, was to strengthen the sense of belonging in the former and current civil community of the university. In addition, the series of festivities offering a multitude of year-long professional and cultural programmes reminded all of the fact that the university, owing to the programmatically high standards it is committed to represent, is an outstanding shaper of scientific and scholarly activity and of training new generations of intellectuals.